Exploring Digital Discourtesy: Impoliteness Strategies In K-Drama Fan Discourse on Social Media - Pratama, Agus Darma Yoga; Suastha, Putu Vania Maharani (Journal of Pragmatics and Discourse Research, 2024)
This study analyzes impoliteness strategies used by netizens in responses to the variety show "Single Inferno 3" on the X app, specifically through the K-Drama Menfess account. Menfess, short for "Mention and Confess," is a term in K-Pop and K-Drama culture, describing messages sent via direct message to auto-bot accounts on platforms like Twitter, where users share opinions on specific topics. "Single Inferno 3" is a popular show among K-Drama fans, and the comments in the Menfess account's replies provide insights into how impoliteness emerges in reactions to South Korean entertainment. Using a descriptive qualitative method, this study examines the types of impoliteness in netizen comments related to the show, drawing on Culpeper's (2011) theory of language impoliteness. The data, collected from comments posted on January 3rd, 2024, reveals that sarcasm or mock politeness is the most prevalent strategy, appearing in 45.45% of cases. Positive impoliteness accounts for 27.27%, negative impoliteness for 18.18%, and bald on-record impoliteness for 9.09%, with no instances of withheld politeness. Sarcasm often involves indirect insults, while negative impoliteness includes belittling remarks. These impoliteness strategies typically arise in contexts where netizens scrutinize the show's participants, reacting to behavior that deviates from expected norms. The study's findings can help social media platforms develop tools to detect and reduce impolite interactions, such as automated moderation systems and user guidelines to promote respectful online discourse.